Staff preparedness for providing palliative and end‐of‐life care in long‐term care homes: Instrument development and validation. Issue 5 (16th January 2018) - Chan, Helen YL; Chun, Gloria KM; Man, CW; Leung, Edward MF
Abstract : Aim: Although much attention has been on integrating the palliative care approach into services of long‐term care homes for older people living with frailty and progressive diseases, little is known about the staff preparedness for these new initiatives. The present study aimed to develop and test the psychometric properties of an instrument for measuring care home staff preparedness in providing palliative and end‐of‐life care. Methods: A 16‐item instrument, covering perceived knowledge, skill and psychological readiness, was developed. A total of 247 staff members of different ranks from four care homes participated in the study. Exploratory factor analysis using the principal component analysis extraction method with varimax rotation was carried out for initial validation. Known group comparison was carried out to examine its discriminant validity. Reliability of the instrument was assessed based on test–retest reliability of a subsample of 20 participants and the Cronbach's alpha of the items. Results: Exploratory factor analysis showed that the instrument yielded a three‐factor solution, which cumulatively accounted for 68.5% of the total variance. Three subscales, namely, willingness, capability and resilience, showed high internal consistency and test–retest reliability. It also showed good discriminant validity between staff members of professional and non‐professional groups. Conclusions: This is a brief, valid and reliable scale for measuring care home staff preparedness for providing palliative and end‐of‐life care. It can be used to identify their concerns and training needs in providing palliative and end‐of‐life care, and as an outcome measure to evaluate the effects of interventional studies for capacity building in this regard.Geriatr Gerontol Int 2018; 18: 745–749